Fluistik Zone: Interactive Digital Media for Learning Static Fluid Concepts in Senior High School Physics - Diraya, Inayatun; Riska, Fati Matur; Sujito (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aims to develop an interactive digital learning media called Fluistik Zone on static fluid material using the 4D development model (Define, Design, Develop, Disseminate). This media covers the subtopic of introductory static fluids, consisting of density, hydrostatic pressure, Pascal's law, and Archimedes' law. The development procedure begins with a needs analysis through teacher interviews and literature reviews, followed by the initial design of Android application-based media equipped with features such as learning videos, interactive quizzes, and Online Active Learning Guide (OALG). Validation was carried out by material experts and media experts with average validity results of 94% and 99% respectively in the very valid category. The practicality assessment by teachers reached 94% in the very well category and student responses showed an average of 85% in the well category. These findings indicate that Fluistik Zone is valid, practical, and interesting for students in supporting physics learning interactively and contextually. This media is designed following the principles of multimedia learning to increase student engagement and understanding. Therefore, Fluistik Zone has the potential as an effective, interesting, and relevant physics learning media innovation to support 21st century learning. However, testing the effectiveness of the media on learning outcomes has not been carried out experimentally and the trial is still limited to one school. Further research is recommended to test the effect of using Fluistik Zone on student learning outcomes through a quasi-experimental design and expand the development to other physics topics and different levels of education.